Salvador Allende: cartoon and monument - Montealegre, Jorge (Meridional. Revista Chilena de Estudios Latinoamericanos, 2014)
Salvador Allende, with self-ironical genius, made a verbal self-portrait that worked both as a cartoon and as a monument. His own physical death, projecting itself into immortality, was the argument of a joke that had his body as a support: "Fresh of a statue" it was jokingly said, referring to the historical transcendence Allende saw in himself. On the other hand, the political opposition, that was aiming to overthrow this government, used the malicious cartoon to build up an atmosphere that was functional to this overthrow that involved President Allend’s death. This article proposes to put into evidence the wide-reaching presence of the image of Allende’s death, both in his own speech and in the cartoons used by the media that participated in his overthrow. The paper also aims to show the symbolical transcendence of the President turned into myth and monument.